Towards Quality Education: Physical Notes VS Digital Notes in Health Expectancy, Eco-Friendly Environment and Notes Accessibility Conditions - Dzulkalnine, Natasha; Azman, Mohamed Nor Azhari; Sumardi, Nur Athirah; Qudus, Nur (Information Management and Business Review, 2023)
Due to the pandemic of COVID-19, students have started using digital technology in learning and note-taking. However, for early adopters, this method might be challenging. Thus, this study objectively examines the preferences of students’ physical or digital note-taking styles. Convenience sampling among 125 students in Universiti Teknologi MARA (UiTM) Selangor branch, Puncak Alam Campus has been used as part of the methodology. Three main variables are selected in assessing the student’s preferences for notes based on the previous study which are Health Expectancy, Eco-Friendly Environment, and Notes Accessibility Conditions. The analysis done is descriptive statistics and correlation analysis using SPSS and SMARTPLS 4. The findings show that the students still prefer physical notes over digital notes. The percentage of preferences is almost the same, and it is expected that in the future the percentage of digital notes taking will shift from physical notes to digital notes. Notes accessibility condition is a significant variable while the other variables are not significant towards student’s preferences for notes. The students are still in the transition process from the era before the pandemic and the post-pandemic era. Thus, it is recommended that the learning style and note-taking style might adopt the combination of physical and digital notes.